Study of interaction in spray between evaporating droplets and turbulence using second order turbulence RANS modelling and a Lagrangian approach. (12th May 2004) - Chrigui, M.; Sadiki, A.; Ahmadi, G.
The objective of this work is to analyse the interaction between evaporating droplets and the turbulent flow of the carrier gas using a second order turbulence RANS modelling in an Euler-Lagrangian approach including two-way coupling. The analysis is performed in a vertical isopropanol polydispersed spray issuing into a co-flowing, heated air stream. The results mainly display the turbulence modulation effects besides the turbulent dispersion of evaporating droplets: 1) The influence of droplet diameter and interface transport on the gas phase turbulence as well as 2) The effect of the droplet evaporation on the mass and heat transfer processes are compared with experimental data. 3) The reciprocal influence of the modification of interface transport by turbulence, i.e., the influence of the turbulent fluctuations of different quantities (such as velocity, temperature, etc.) on the droplet evaporation (through the mass and heat evaporation rates, the droplets diameter distribution) are computed and discussed.